UJI EFIKASI FUNGISIDA PADA ISOLAT YANG BERASOSIASI DENGAN GEJALA PENYAKIT PADA BIBIT KALIANDRA - Reftriasih Vrika; Bayo Alhusaeri Siregar (JURNAL BIOSENSE, 2026)
The kaliandra plant is utilized by industry and its advantages are proven by its high calorific value. However, in its cultivation, kaliandra is often attacked by leaf spot disease caused by pathogenic fungi. To address this issue, methods are needed to suppress these pathogenic fungi. Fungicides are one of the control measures required to reduce the pressure of pathogenic fungal development. This study aims to determine the effectiveness of various fungicides against pathogenis fungal isolates that cause leaf spot in kaliandra seedlings. The research was conducted using a systemic in vitro method with treatments consisting of a control (without fungicide) and five types of fungicides. The pathogenic fungal isolates used were isolates previously obtained from kaliandra plants at PT. Arara Abadi. The identification results showed that the fungicide octave® was the most effective in supressing and inhibiting fungal hyphal growth. The fungicides primaclink® and wuz® were still effective in supressing fungal growth but did not inhibit it. Meanwhile, the fungicides kuproxat®, besromil®, and flasher® were not effective in supressing the growth of the pathogenic fungal isolates.